The prospect and challenges of renewable hydrogen production in Iraq - Alsaffar M.A.; Ayodele B.V.; Abdel Ghany M.A.; Yousif Shnain Z.; Mustapa S.I. (Institute of Physics Publishing, 2023)
The energy demand in Iraq has increased in the past decade as a result of growth in population and industrialization. Although, most of the energy demand is being met using energy derived from fossil fuels, which are fast depleting and have the problem of emission of greenhouse gases when combusted. Recently, there have been an increasing awareness in the quest for alternative source of cleaner and sustainable energy production. One of such alternatives is hydrogen energy, which has been tagged as the energy of the future with zero-emission when combusted with oxygen. Moreover, hydrogen has wide applications in electrochemical cells for electricity production or as fuel in internal combustion engines for powering vehicles. The present study gives an overview of the prospect and challenges of renewable hydrogen production in Iraq. Moreover, the availability of the different feedstocks for the production of renewable hydrogen as well as the state-of-the-art in Iraqi context were examined. The prospect and challenges in the production of renewable hydrogen in Iraq were also presented. Published under licence by IOP Publishing Ltd.